Dialektika Sains, Tradisi dan al-Qur’an: Representasi Modernitas dalam Tafsir Rahmat karya Oemar Bakry - Mahbub Ghozali (AL QUDS : Jurnal Studi Alquran dan Hadis, 2021)
Dialectic of Science, Tradition and the Qur'an: Representation of Modernity in Tafsir Rahmat by Oemar BakryThe problem of interpretation in Indonesia which still refers to popular variation works impacts other understanding works ignored. This rejection has implications for the lack of disclosure of the peculiarities of an interpretation that can contribute to determining the method of interpretation in Indonesia. Tafsir Rahmat by Oemar Bakry is one of the interpretations that are rarely expressed in its content so that aspects of modernity are not revealed. This study aims to show parts of modernity in the Tafsir Rahmat in the form of dialectics between science, tradition, and the Qur'an. This research uses qualitative methods with content analysis as a data analysis tool. This research shows that Bakry provided a different view in the translation process by using modern terms to offer a breadth of understanding and ease. Science and technology are used to find wisdom (hikmah) and proving the truth of the Quran. The spirit of renewal carried by Bakry is also evident from the critical response to the traditions carried out by the people of Indonesia. The peculiarities in interpretation and translation that Bakry did were enough to make Tafsir Rahmat an object of study for dialectics to occur among researchers. It also impacts the dissemination of the content of this interpretation faster and affects the popularity of Tafsir Rahmat.